Towards Overcoming the Human Development Barrier in Ghanaian Libraries - Tiamiyu, M.A. (Ghana Library Journal, 1997)
Libraries have traditionally prided themselves in the sizes of, and the potential infonnation in, their collections of documents of various kinds. And, in this infonnation technology age, libraries are also constantly remjnded that they must keep pace with new technologies for information storage and retrieval, for information resource networking, for library management, and for public services . However, beyond collection sizes and content, and beyond technological artifacts, the ability of a library to provide effective services to its clientele depends critically on the experience, motivation and management of its human resources . Human resources make things happen in libraries, not items in the collection, not technological artifacts . Collection items and technological artifacts provide potential capabilities for processing and russeminating infonnation. But human resources detennine whether these potentials can be harnessed to satisfy the infonnation needs of library patrons.